Electron-hole asymmetry in high-Tc cuprates from theoretical viewpoints - T. Tohyama (Iranian Journal of Physics Research, 2006)
Asymmetric features of various physical quantities in the normal and superconducting states between hole- and electron-doped cuprate high-temperature superconductors have been an issue of debate for a long time. Their exploration is very important for the understanding not only of the mechanism of high-Tc superconductivity but also of the nature of doped-Mott insulators. Presented in this review is the present status of theoretical understanding of the electronic states in hole- and electron-doped high- Tc cuprates as well as the origin of the electron-hole asymmetry of the electronic states. In particular, it is shown that numerically exact diagonalization calculations for small clusters in a t-J model with long-range hoppings, t and t nicely reproduce the electron-hole asymmetry observed experimentally in various quantities and thus make it possible to extract the physical origin of the asymmetry. These results give a deep insight on the asymmetric behaviors in hole- and electron-doped high-Tc cuprates and on the nature of doped Mott insulators.